Both English- and Spanish-Language Anterior Cruciate Ligament Reconstruction Online Patient Education Materials Are Written at Higher-Than-Recommended Reading Levels - Jacob S. Ghahremani, B.A.; Michael Chapek, B.A.; Virginia Xie, B.A.; Tanya Watarastaporn, B.S., M.S.; Nala A. Al-Khatib, B.S.; Ronald A. Navarro, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To examine the overall reading levels of anterior cruciate ligament reconstruction online patient education materials (OPEMs) written in English and Spanish. Methods: We conducted Google searches for OPEMs using “ACL surgery” and “cirugía LCA” as English and Spanish search terms, respectively. Several measures of readability were used to analyze 25 English-language OPEMs (Flesch Reading Ease, Flesch Reading Ease Grade Level, Flesch-Kincaid Grade Level, Coleman-Liau Index, Gunning Fog Index, and Simple Measure of Gobbledygook) and 25 Spanish-language OPEMs (Fernández-Huerta Index, Fernández-Huerta Grade Level, and Índice de Legibilidad de Flesch-Szigriszt). English- and Spanish-language OPEMs were compared based on mean overall grade level and number of OPEMs written below a seventh- or ninth-grade reading level. Results: English-language OPEMs showed a higher mean overall grade level than Spanish-language OPEMs (10.48 ± 1.86 vs 8.64 ± 1.22, P < .001). No significant differences were noted in the number of OPEMs written below a seventh-grade reading level. However, significantly more Spanish-language OPEMs were written below a ninth-grade reading level compared with English-language OPEMs (56% vs 16%, P = .003). Conclusions: Although Spanish-language OPEMs were written at a lower reading level, average readability for both English- and Spanish-language OPEMs was significantly higher than the recommended level. Across both languages, only a single English-language webpage met the American Medical Association–recommended sixth-grade reading level. More Spanish-language articles were written at or below the average adult reading level in the United States. Clinical Relevance: It is imperative that patient educational materials be written at a reading level that is understood by the most patients. This is especially true for OPEMs, when a medical provider is not present to answer questions. Therefore, it is important to evaluate the reading level of OPEMs to determine whether they are written at an appropriate level for the best patient understanding.